Nontoxic goiter: causes, clinical evaluation and management - Thakkar, Dhaval B.; Deshmukh, Satish D.; Akhtar, Murtaza (International Surgery Journal, 2018)
Background: Thyroid diseases are the commonest endocrine disorders worldwide and India is no exception. Goiter may be generalized or localized, toxic or nontoxic. The present study is being carried out in a government notified endemic area to study the etiology and surgical management with postoperative complications in patients with nontoxic goiter. Methods: A observational study was carried out at a tertiary care academic hospital. Patients with a clinically diagnosed nontoxic goiter with normal T3, T4 and TSH values were included in the study. The study subjects underwent relevant investigations and surgical intervention. The outcome factors were histopathology of the surgically removed gland and postoperative complications. Results: A total of 67 patients of nontoxic goiter were enrolled. The mean age of the patients was 33.3±11.1 years with female preponderance. The mean duration of the thyroid swelling was 2+/- 2 years. Hemithyroidectomy was most common surgery (68.7%) carried out. A majority (88%) of resected thyroid specimens were benign histopathologically as colloid goiter. An intergroup analysis was carried out between metabolic, autoimmune and neoplastic etiologies. Neoplastic etiology was significantly associated with smooth surface and hard consistency of the gland. Autoimmune goiter had significantly less than 12 months duration and painful. The postoperative complications observed were hypothyroidism (22.4%), hypoparathyroidism (10.5%), RLN palsy (6%) and SSI (3%). Conclusions: Benign pathology was commonly seen with nontoxic goiter. Hypothyroidism and Hypoparathyroidism were the most frequent postoperative complications.